Pengaruh Pemberian Sisa Hasil Usaha (SHU) Terhadap Partisipasi Anggota Pada Koperasi Pegawai Republik Indonesia Bangkit Di Rangkasbitung - Euis Ajizah; Virgoyanti .; dede suharna; Maesaroh . (E-Journal Studia Manajemen, 2012)
High participation of cooperative members in utilizing the services of all goods, services, available dikoperasi ultimately improve the quality and quantity of the best service and excellence by cooperative companies. Time Results of Operations (SHU) is important to be known by members of the cooperative. Because members are owner and user of cooperative services. This research uses descriptive quantitative method, the population in this study are the financial statements of the cooperative to get up and use the sample according to the cooperative's financial statements during the five (5) years ie from 2007 to 2011. The study found that the accepted hypothesis is the alternative hypothesis, that is to say there is influence between the granting of Business (SHU) The Member Participation Employees Cooperative Republic of Indonesia (KPRI) Rise in Rangkasbitung.